Choosing efficient production diversification in digitalization conditions - D. V. Abramov (Вестник Северо-Кавказского федерального университета, 2023)
Introduction. The key motive of this research is the global trends of bipolar nature: economic isolation and challenges in international cooperation, a versatile external influence on opportunities and the emergence of new risks in the organization. Goal. The purpose of the article is to analyze and identify promising methods of diversification formation in order to achieve the maximum efficiency. The conceptual apparatus of goal-setting (goal, landmark, development) has been clarified. The key provisions of the strategy and their types are reflected, the classification of the types of diversification strategy is clarified, a close connection with integration processes in regression from certain features is determined. The measure of the expediency of choosing the type is determined, based on strengthening competitiveness and investment attractiveness. The understanding of management levels is revealed. Materials and methods. This study is based on the analysis and identification of promising methods for the formation of diversification in order to achieve the maximum possible efficiency. At the same time, the author admits the possibility of achieving these goals through the development and further dynamics of the growth of the organization or the choice of tactics for building a stable economic system capable of overcoming external stimuli. Results and discussion. The basis of such judgments is the currently available opportunity and perspective of management in choosing alternative ways to achieve efficiency in entrepreneurial (production) activities under conditions of general digitalization. Conclusion. The fundamental factor of the organization development has been identified – sustainability, consisting of separate components representing a common understanding of the possibility.